Drawings pen and ink - McEwen, Rolf. ([Great Britian] : [CreateSpace Independent Publishing Platform], 2018)
This collection of pen and ink drawings explores subjects including old European streets, towns, and people. Images include old buildings, riders on horseback, carriages drawn by horse, and attractive churches. Some lovely costumes are also on display. Pen and ink drawings require particular talent.
Keywords: Pen drawing -- Technique